In-Situ Remediation of Lead–Zinc Polymetallic Mine Contaminated Soils by MnFe2O4 Microparticles. Issue 3 (2nd April 2016) - Yuan-Jie, Li; Lin, Li; Gui-Ling, Wang; Shuai, Song; Yan-Ying, Sun
ABSTRACT: In-situ remediation is a practical approach to remediate soils contaminated with heavy metals. The MnFe2 O4 microparticles (MM) were prepared for the in-situ remediation of contaminated soils from a lead–zinc polymetallic mine in Inner Mongolia province, China. The effects of MM dosage, pH on remediation efficiency, were determined with static vibration leaching experiment, and the release risk of heavy metals of treated soil was studied by column leaching experiment. The results showed that the leached Cu, Pb, Zn, and As concentration decreased drastically with increasing MM dosage, when the dosage was lower than 10 g/kg. Moreover, the decrease of pH caused increase of leached concentration of Cu, Pb, Zn, but slight decrease of leached As concentration. For the amended soil, concentrations of leached heavy metals were lower than Grade III limit of Chinese Environmental Quality Standards for Ground and Surface water (GB3838-2002) under simulated acid rain leaching condition. In comparison with non-amended soils, the total amount of Cu, Pb, Zn, and As release from amended soils was reduced by 93.6%, 69.2%, 57.0%, and 99.7%, respectively. The MM is a kind of promising amendment for heavy metals contaminated soil.